Screening for Resistance Against Ralstonia Solanacearum in Commercially Available Colombian Potato Varietiest - Christian David Vargas; Mauricio Soto-Suárez; Paola Zuluaga (Ciencia y Tecnología Agropecuaria, 2023)
Ralstonia solanacearum, the causal agent of bacterial wilt, is one of the most devastating bacterial diseases worldwide. In potatoes and many other commercial species such as tomato, banana, plantain, and eggplant, among others, there is a lack of efficient strategies to control this pathogen. Therefore, using resistant cultivars might be the best strategy to prevent this disease. However, breeding for bacterial wilt resistance is challenging since latent infections pose a significant limitation when evaluating resistance to this disease in plant germplasm. Part of the diversity of potato genetic resources is maintained in the Colombian Central Collection (CCC) of potatoes, Corporación Colombiana de Investigación Agropecuaria (Agrosavia). With its 2069 accessions, the CCC is a good source for plant breeding programs. As a first attempt to identify bacterial wilt resistant/tolerant potato sources, 11 commercially available potato varieties were evaluated, representing Andigena and Phureja materials from the CCC. To this end, plants were drench-inoculated with R. solanacearum. This strain was able to cause severe disease in six of the 11 accessions tested. Thus, five highly R. solanacearum-resistant accessions were identified. These results represent a preliminary assessment for identifying bacterial wilt resistance sources that will contribute to establishing a potato breeding program to face this devasting pathogen before it arrives 70 Colombia.